Migrating from the Library of Today to the Library of Tomorrow Re- or E-volution? - Ershova, Tatiana V.; Hohlov, Yuri E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This paper discusses library development in the changing environment arising within the forthcoming Information/Knowledge Society. The role of the library as a social institution is examined in the context of the evolution of the whole literary and knowledge system. Ideas about conceptual changes to be introduced by the library in order to respond to challenges of the Information Age are presented. Approaches are offered that could help the library evolve from an institution that conserves and provides access to a patrimony to become an inalienable part of a distributed global knowledge warehouse. The paper includes the following sections: (1) The World in Change: Advent of a Knowledge Society: (2) Evolution of the Literary and Knowledge System; (3) The Library in a New Information Environment: Transformation Challenges; (4) Development Strategy: Towards the Hybrid and Digital Library; and (5) Library Policies for Change. (Contains 11 references.) (Author/MES)
Availability: For full text: http://www.ifla.org/IV/ifla66/papers/063-110e.htm.
ERIC Note: In: IFLA Council and General Conference: Conference Proceedings (66th, Jerusalem, Israel, August 13-18, 2000); see IR 057 981.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change; Electronic Libraries; Information Technology; Library Development; Library Policy; Library Role; Library Services; Information Society -- Technological Change; Information Age; Reports, Descriptive; Speeches/Meeting Papers